Can Keff be assumed as the driving force for fatigue crack growth? - J.T.P. Castro; M.A. Meggiolaro; J.A.O. González (Fracture and Structural Integrity)
This work raises some new questions about the validity of blindly assuming that Elber’s effective stress intensity factor is the actual fatigue crack driving force, and that as so it can be used to explain all load sequence effects on fatigue crack growth (FCG). Although plasticity-induced crack closure can be a quite reasonable heuristic explanation for many non-elementary FCG behaviors, it has some limitations that cannot be ignored. In fact, this never settled discussion is particularly important for the simulation of FCG lives under real service loads, a most important practical issue. After arguing that Keff can spoil the use of the most important similitude principle in FCG problems, simple but convincing experimental data that cannot be explained by this classical idea is presented here. This data involves the shape of fatigue crack fronts and the FCG behavior under nominally plane stress and plane strain conditions.